High-efficiency purification of CH4 and H2 energy sources enabled by a phosphotungstic acid-supported Os single-atom catalyst - Li-Long, Zhang; Zheng, Ji; Gu, Jinxing; Huang, Zhuochun; Lu, Linguo; Hu, Li; Chen, Zhongfang; Yang, Song (Journal of materials chemistry. A, Materials for energy and sustainability, 2023)
Methane (CH4) and hydrogen (H2) show promise as low-carbon energy sources, but their impurities, including H2 and CO, pose challenges for storage and use. To address these challenges, a robust purification protocol for CH4 and/or H2, combined with the catalytic conversion of impurities into CO2 and H2O, is a compelling solution. In this work, we investigated 11 phosphotungstic acid (PTA)-supported single-atom catalysts (SACs) by density functional theory (DFT) computations. Os1/PTA SACs exhibited superior catalytic activity, and the ease of oxidation follows the CO > H2 > CH4 order. It facilitated efficient purification of CH4 in solvents such as water, MeOH, and various others. For H2 purification, Os1/PTA SACs demonstrated excellent performance in gas, water, and MeOH. Notably, in water and MeOH, it selectively removed CO without consuming H2 with low free energy barriers. The strong Os-PTA interactions and charge transfer mechanism contributed to its exceptional catalytic activity. Our findings shed light on SAC behavior and their potential for efficient CH4 and H2 purification. By addressing impurity challenges and improving clean energy utilization, these findings contribute to the development of sustainable energy technologies.